Addition of two new genera—Marcstadlera gen. nov. and Neoclypeosphaerella gen. nov. (Mycosphaerellaceae)—based on polyphasic evidence - Singh, Gargee; Rajwar, Soumyadeep; Khatoon, Sahana; Yadav, Sanjay; Kumari, Pooja; Singh, Raghvendra; Kumar, Kamalesh; Mall, Smriti; Singh, Paras N.; Kumar, Shambhu; Braun, Uwe (Frontiers in Cellular and Infection Microbiology, 2025)
During a survey of foliicolous fungi in India, two interesting anamorphic hyphomycetous fungal specimens were collected from infected leaves of Calotropis spp. and Mallotus philippensis. Calotropis spp. produce fascicles of conidiophores from stromata, accompanied by secondary superficial hyphae bearing solitary conidiophores. The specimen on Mallotus philippensis resembled Mycovellosiella, characterized by secondary superficial hyphae bearing micronematous to semi-macronematous, mononematous, unbranched, and aseptate conidiophores. A polyphasic approach—including morphological, cultural, and multilocus phylogenetic analyses (LSU-Rpb2-ITS), coupled with genealogical concordance phylogenetic species recognition—identified its relationship with cercosporoid fungi within the family Mycosphaerellaceae. The analysis confirmed that these fungal specimens represent distinct lineages without known morphological or DNA sequence counterparts. Consequently, two new genera are proposed: Marcstadlera and Neoclypeosphaerella, with M. malloti comb. nov. and N. calotropidis comb. nov. as their respective type species. Additionally, Clypeosphaerella calotropidis, Clypeosphaerella quasiparkii, and Pseudocercospora malloti are recognized as new synonyms. Several genera in the Mycosphaerellaceae, including Marcstadlera and Neoclypeosphaerella, are monophyletic. The ultrastructure of the conidiogenous loci and hila differs between these two genera. In Marcstadlera, the loci are cylindrical or peg-like, truncate at the apex, while the conidial base is narrowly obconically truncate. In Neoclypeosphaerella, the loci are slightly protuberant and surrounded by a circular rim-like structure, forming a truncated apex with a centrally positioned small apical depression. The conidial base is obconically truncated and also surrounded by a circular rim-like structure.